WORKING ON ERRORS IN ORAL SPEECH (Ta'limning zamonaviy transformatsiyasi, 2024)
This article is about working on oral speech performance. In this article, you can learn how problems arise in oral speech and how to fix them. It explores how to get better at speaking by fixing mistakes. It talks about the challenges of correcting errors during speaking compared to writing. By trying different ways to fix mistakes and considering how students feel, teachers can help everyone improve at speaking confidently.